Effect of electronic cigarette usage on oral health: a 6-month prospective study - Ismail, Ahmad Faisal; Ghazali, Aini Fatimah; Daud, Azlina (Institute of Medico-Legal Publications, 2019)
A growing trend towards a new type of alternative device where cigarette smokers use electronic cigarette (e-cigarette) to receive nicotine is a concern to global health. Questions have been raised about the safety of the prolonged used of e-cigarette as it claims as the system to substitute nicotine from tobacco. However, to date there has been little documented evidence regarding the oral health effects of e-cigarette users. The objective of this study was to evaluate the oral health status of e-cigarette users based on time effect. This observational, cohort study conducted at Kulliyyah of Dentistry, International Islamic University Malaysia, involved 45 participants. Oral health examination was conducted by a single trained examiner at baseline and 6-month according to the World Health Organization (WHO) criteria. Dental caries was evaluated using the DMFT index, while the periodontal parameters that were assessed used plaque, gingivitis, gingival bleeding, and calculus indices. The results were compared using Paired t-test, the outcomes of which were significant for Gingival Index (p=0.048), Calculus Index (p=0.034), and DMFT Index (p=0.002). In conclusion, e-cigarette posed a detrimental effect on oral health status with increased caries prevalence and poorer gingival health.